Longitudinal changes in anthropometry and body composition in university freshmen. Issue 4 (19th May 2017) - Hootman, Katie C.; Guertin, Kristin A.; Cassano, Patricia A.
ABSTRACT: Objective : We investigated predictors of weight gain in college freshmen.Participants : A longitudinal cohort study followed a representative sample of freshmen ( N = 264) from 8/2011 to 6/2012.Methods : Repeated measurements of anthropometry, dual-energy X-ray absorptiometry (DXA), physical activity, and diet were collected. We investigated predictors of 9-month weight gain using regression models.Results : 172 participants completed follow-up: 75% gained >0.5 kg. Mean weight change was +2.3 kg ( SD 3.2) and +2.0 kg ( SD 3.2) and mean adiposity change was +1.3% ( SD 1.6) and +0.7% ( SD 2.2) in men and women, respectively. In participants gaining >0.5 kg, weight increased 5.6% and body fat increased 1.6%. Anthropometric change in men occurred in the first semester, while women increased in both semesters. Leaner DXA-defined body composition at baseline was consistently associated with greater weight gain ( p -values 0.029–0.049).Conclusions : Freshman weight gain is common and reflects increased adiposity. Leaner body composition at the beginning of college predicted greater weight gain in men and women during the first year of college.